Semiprime gamma rings with orthogonal reverse derivations - Dey, Kalyan Kumar; Paul, Akhil Chandra; Rakhimov, Isamiddin Sattarovich (Academic Publications, 2013)
In this paper, the deﬁnition of orthogonal reverse derivations is given. Some characterizations of semiprime gamma rings are obtained by means of orthogonal reverse derivations. We also investigate conditions for two reverse derivations to be orthogonal.